How capital structure influences diversification performance: A transaction cost perspective. (25th June 2013) - O'Brien, Jonathan P.; David, Parthiban; Yoshikawa, Toru; Delios, Andrew
<x xml:space="preserve">Abstract</x> Extant theories agree that debt should inhibit diversification but predict opposing performance consequences. While agency theory predicts that debt should lead to higher performance for diversifying firms, transaction cost economics (TCE) predicts that more debt will lead to lower performance for firms expanding into new markets. Our empirical tests on a large sample of Japanese firms support TCE by showing that firms accrue higher returns from leveraging their resources and capabilities into new markets when managers are shielded from the rigors of the market governance of debt, particularly bond debt. Furthermore, we find that the detrimental effects of debt are exacerbated for R&D intensive firms and that debt is not necessarily harmful to firms that are either contracting or managing a stable portfolio of markets. Copyright © 2013 John Wiley & Sons, Ltd.